PREVALENCE OF DENTAL CARIES AMONG SMOKERS OF A TERTIARY CARE HOSPITAL OF LAHORE - ZULFIQAR, H; FATIMA, M; SADDIQUE, H; TASNEEM, SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Dental caries is a common chronic oral health condition globally, with an increased prevalence among smokers. Smoking contributes to caries risk by affecting saliva production, oral microbiota, and oral hygiene practices. In Pakistan, where smoking is prevalent. Objective: This study aims to assess the prevalence of dental caries among smokers attending a tertiary care hospital in Lahore. Methods: A cross-sectional study was conducted at Jinnah Hospital, Lahore, from January to July 2024. The sample included 100 adult smokers aged 18 years and above. Data on demographics, smoking frequency, oral hygiene practices, and dental caries were collected using structured interviews and clinical examinations. Caries severity was assessed using the Decayed, Missing, and Filled Teeth (DMFT) index. Statistical analyses, including chi-square tests, were conducted to explore associations between smoking habits and caries prevalence. Results: The majority of participants were aged 26-35 (30%), with 35% smoking 6-10 cigarettes daily. Oral hygiene practices were suboptimal, with only 25% brushing twice daily, and 15% reporting no regular hygiene routine. The prevalence of dental caries was strongly correlated with smoking frequency and duration. Participants smoking more than 21 cigarettes daily had an 80% caries prevalence, while those with a smoking history of over 16 years had a mean DMFT score of 7.6. These results align with previous studies linking smoking with higher caries risk and severity. Conclusion: The study highlights a high prevalence of dental caries among smokers, with significant associations between smoking frequency, duration, and caries severity. These findings underscore the need for preventive dental health interventions, including smoking cessation programs and targeted oral hygiene education, to mitigate the burden of dental caries in this high-risk population.